Preparation method and application of ZJM-9 molecular sieve containing phosphorus and aluminum components

By preparing ZJM-9 molecular sieve containing phosphorus aluminum components, the problem of easy occupation of existing six-membered ring molecular sieve pores is solved, and the effect of selective adsorption of water at room temperature is achieved, which improves the dehydration efficiency and reduces energy consumption.

CN116002712BActive Publication Date: 2025-02-18ZHEJIANG UNIV

Patent Information

Application Number
CN202310000217.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-02
Publication Date
2025-02-18
Estimated Expiration
2043-01-02

AI Technical Summary

Technical Problem

The existing six-membered ring molecular sieve pores are easily occupied by organic template agents or inorganic ions, resulting in the loss of adsorption and separation capacity, and requires high temperature to consume a large amount of energy during the dehydration process.

Method used

By preparing a ZJM-9 molecular sieve containing aluminum phosphorus, the template agent solution method combined with hydrothermal reaction is used to form a pure aluminum phosphate molecular sieve with a new topological structure, and the organic structure orientation is removed through high-temperature calcination and water washing treatment. agent, retaining the molecular sieve skeleton structure.

Benefits of technology

The ZJM-9 molecular sieve selectively adsorb water at room temperature is realized, which enriches the types of molecular sieve, improves the dehydration efficiency of gas and alcohols, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116002712B_ABST
    Figure CN116002712B_ABST
Patent Text Reader

Abstract

The present invention relates to molecular sieve preparation technology, and aims to provide a preparation method and application of a phosphorus-aluminum-containing ZJM-9 molecular sieve. The method includes: adding an aluminum source, a phosphorus source and a silicon source to a template solution under stirring, uniformly mixing to form a gel; performing a hydrothermal crystallization reaction, filtering, washing and drying the product to obtain a ZJM-8 molecular sieve; performing high-temperature roasting to obtain a roasted ZJM-8 molecular sieve; mixing it with water, filtering, drying and roasting it twice at 100 to 800 ° C to obtain a phosphorus-aluminum-containing ZJM-9 molecular sieve product. The ZJM-9 molecular sieve provided by the present invention is a new type of phosphorus-aluminum molecular sieve product, which enriches the types of molecular sieves. The molecular sieve can selectively adsorb water at room temperature, and therefore plays an important role in the dehydration field of gas and alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of molecular sieves, and in particular to a preparation method and application of a ZJM-9 molecular sieve containing phosphorus and aluminum components. Background Art

[0002] Industrial gases often contain a lot of water during the production process, which will make equipment corrosion or catalyst poisoning in the downstream process easy to occur. Therefore, poor dehydration effect will affect production capacity and equipment life. Therefore, in order to make it operate stably for a long time, the water content in the mixed gas must be strictly controlled during the production process. Nowadays, solid desiccants such as 3A molecular sieve, 4A molecular sieve and 13X molecular sieve are commonly used in industry for drying. However, these molecular sieves have a strong effect on water. The dehydration temperature of 3A molecular sieve is as high as 250℃, and the dehydration temperature of 13X molecular sieve is even as high as 350℃, which means that the recovery of desiccant requires huge energy consumption.

[0003] Aluminophosphate molecular sieves are a type of porous material with aluminum phosphate as the skeleton structural unit. People are always committed to synthesizing molecular sieves with more than or equal to eight-membered rings, and even synthesizing some molecular sieves with ultra-large pores. However, existing molecular sieves with less than eight-membered rings are considered to be non-porous molecular sieves and have no meaning in practical applications. Therefore, the synthesis of small-pore molecular sieves is often ignored.

[0004] The special size and stability of the six-membered ring pores in the molecular sieve are conducive to the adsorption and separation of water in gases and organic vapors, while many gas molecules larger than water molecules cannot enter the molecular sieve pores. Therefore, the six-membered ring molecular sieve plays an important role in the field of water adsorption and separation. However, the existing six-membered ring molecular sieve pores are often occupied by some organic templates or inorganic ions, and it is almost impossible to remove the organic templates or inorganic ions from the six-membered ring molecular sieve. Therefore, the existing six-membered ring molecular sieve does not have the ability of adsorption and separation because the pores are blocked.

[0005] Based on the above reasons, the present invention intends to provide a six-membered ring molecular sieve with adsorption separation capability. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a preparation method and application of ZJM-9 molecular sieve containing phosphorus and aluminum components.

[0007] To solve the technical problem, the solution of the present invention is:

[0008] The present invention provides a method for preparing a ZJM-9 molecular sieve containing phosphorus and aluminum components, comprising the following steps:

[0009] (1) preparing a template solution by combining a template and water, and sequentially adding an aluminum source, a phosphorus source and a silicon source under stirring, and uniformly mixing to form a gel; wherein the molar ratio of the aluminum source calculated as Al2O3: the phosphorus source calculated as P2O5: the silicon source calculated as SiO2: the template: the water is 1: (0.7-1.3): (0-0.6): (0.5-1.5): (20-100);

[0010] (2) transferring the gel to a hydrothermal reactor for hydrothermal crystallization reaction; the reaction temperature is 180 to 250° C., and the reaction time is 1 to 7 days;

[0011] (3) filtering, washing and drying the product to obtain ZJM-8 molecular sieve;

[0012] (4) calcining the ZJM-8 molecular sieve at 400-800° C. for 2-10 h to obtain a calcined ZJM-8 molecular sieve;

[0013] (5) Mixing the calcined ZJM-8 molecular sieve with water and stirring evenly at room temperature; filtering and drying the mixture, and then calcining it for a second time at 100 to 800° C. for 2 to 10 hours to obtain a ZJM-9 molecular sieve, i.e., a ZJM-9 molecular sieve product containing phosphorus and aluminum components.

[0014] As a preferred embodiment of the present invention, the aluminum source is at least one of boehmite, aluminum hydroxide, aluminum oxide or aluminum isopropoxide.

[0015] As a preferred embodiment of the present invention, the phosphorus source is phosphoric acid.

[0016] As a preferred embodiment of the present invention, the silicon source is at least one of silica sol, fumed silica, solid silica gel or tetraethyl silicate.

[0017] As a preferred embodiment of the present invention, the template is 1,4-hexaethylbutylammonium hydroxide, and the structural formula is as follows:

[0018]

[0019] The present invention further provides the use of the ZJM-9 molecular sieve containing phosphorus and aluminum components prepared by the above method as an adsorbent.

[0020] Description of the invention principle:

[0021] The specific structure of the molecular sieve is determined by the X-ray diffraction pattern (XRD), and different zeolite molecular sieves have different XRD spectrum characteristics. Currently known molecular sieves all have their own characteristic XRD spectra, so by comparing the XRD spectrum of the molecular sieve sample with the XRD spectrum in the known molecular sieve database, it can be known whether the molecular sieve has a new molecular sieve topology.

[0022] The present invention first prepares a new type of ZJM-8 sub-sieve, and compares its XRD diffraction pattern with all known structures, and finds that the molecular sieve is a pure aluminum phosphate molecular sieve with a brand-new molecular sieve topology. Currently, there is no pure aluminum phosphate molecular sieve with the same topology as ZJM-8.

[0023] Based on the ZJM-8 molecular sieve, the present invention continues to obtain the calcined ZJM-8 molecular sieve by high temperature calcination. The latter removes the organic structure directing agent (OSDA) filled between the molecular sieve channels relative to the ZJM-8 molecular sieve, but still retains the molecular sieve framework structure. After refining the XRD diffraction pattern of the calcined ZJM-8 molecular sieve, it can be concluded that the molecular sieve structure is the same as the ZJM-8 molecular sieve structure.

[0024] The present invention is based on further water washing and secondary calcination of the calcined ZJM-8 molecular sieve to transform the ZJM-8 molecular sieve into a ZJM-9 molecular sieve. The molecular sieve has the ability to selectively adsorb water, and the fact that water molecules can enter the pores indicates that the pores of the ZJM-9 molecular sieve are open.

[0025] The present invention plays an important role in exploring the synthesis of a new framework structure of molecular sieves, which is specifically manifested in that after refining the XRD diffraction pattern of the ZJM-9 molecular sieve, it is found through comparison that the product has a molecular sieve structure different from that of the ZJM-8 molecular sieve after one calcination. At the same time, there is currently no pure aluminum phosphate molecular sieve with the same topological structure as the ZJM-9 molecular sieve prepared by the present invention. Therefore, the ZJM-9 molecular sieve is a new type of aluminum phosphate molecular sieve.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The ZJM-9 molecular sieve of the present invention is a new type of phosphorus aluminum molecular sieve, which enriches the types of molecular sieves.

[0028] 2. The ZJM-9 molecular sieve prepared by the present invention can selectively adsorb water at room temperature, and therefore plays an important role in the field of gas and alcohol dehydration. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD diagram of the ZJM-8 molecular sieve material prepared in Example 1 of the present invention.

[0030] Figure 2 This is a SEM image of the ZJM-8 molecular sieve material prepared in Example 1 of the present invention.

[0031] Figure 3 This is the XRD diagram of the calcined ZJM-8 molecular sieve material prepared in Example 1 of the present invention.

[0032] Figure 4 This is a SEM image of the calcined ZJM-8 molecular sieve material prepared in Example 1 of the present invention.

[0033] Figure 5 This is the XRD diagram of the ZJM-9 molecular sieve material prepared in Example 1 of the present invention.

[0034] Figure 6 This is a SEM image of the ZJM-9 molecular sieve material prepared in Example 1 of the present invention.

[0035] Figure 7 This is the water adsorption curve of the ZJM-9 molecular sieve material obtained in Example 1 of the present invention.

[0036] Figure 8 This is the H2O / CH4 competitive adsorption curve obtained by the ZJM-9 molecular sieve in the gas dehydration example in Example 1.

[0037] Fig. 9 This is the H2O / CH3OH competitive adsorption curve obtained by the ZJM-9 molecular sieve in the alcohol dehydration example in Example 1.

[0038] Fig.10 This is the N2 adsorption curve of the ZJM-8 molecular sieve after calcination in Example 1.

[0039] Fig.11 This is the N2 adsorption curve of the ZJM-9 molecular sieve in Example 1.

[0040] Fig.12 This is the H2O adsorption curve of the ZJM-8 molecular sieve after calcination in Example 1.

[0041] Fig.13 This is the H2O adsorption curve of the ZJM-9 molecular sieve in Example 1. DETAILED DESCRIPTION

[0042] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be noted that the method of the present invention is not limited to the following examples and cannot limit the scope of protection of the present invention.

[0043] Example 1

[0044] 3.60 g (concentration of 0.89 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 0.69 g of deionized water were placed in a 25 ml beaker, 0.47 g of boehmite (70 wt% Al2O3) was added and stirred evenly, and then 0.74 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; then the solution was poured into a hydrothermal reactor and crystallized at 200°C for 3 days.

[0045] In the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: template: water is 1:1:1:40.

[0046] After the crystallization is completed, the hydrothermal reactor is cooled to room temperature, and the obtained molecular sieve is washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve is a new pure aluminum phosphate molecular sieve ZJM-8, such as Figure 1 As shown, the electron microscope photo shows that the molecular sieve is in the shape of hexagonal blocks.

[0047] The sample was calcined at 550℃ for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, such as Figure 3 At the same time, the electron microscope photo shows that the molecular sieve is still in the shape of hexagonal blocks.

[0048] Mix 1g of calcined ZJM-8 molecular sieve with 20g of water and stir at room temperature for 24 hours; filter and dry, and then calcine again at 550℃ for 4 hours to obtain molecular sieve ZJM-9. Then grind into powder for XRD analysis. The molecular sieve is a new pure aluminum phosphate molecular sieve ZJM-9. Figure 6 As shown, the electron microscope photo shows that the molecular sieve is in the shape of hexagonal blocks.

[0049] In the XRD diffraction data of the ZJM-8 molecular sieve obtained in this example, the 2θ angle of the strongest peak in the range of 5 to 40° is 20.70±0.20; the X-ray diffraction spectrum includes at least the following X-ray diffraction peaks:

[0050]

[0051] Among them, the incident ray of X-ray diffraction is Cu Kα1.

[0052] The X-ray diffraction pattern of the calcined ZJM-8 molecular sieve obtained in this example includes at least the following X-ray diffraction peaks:

[0053]

[0054]

[0055] Among them, the incident ray of X-ray diffraction is Cu Kα1.

[0056] The X-ray diffraction spectrum of the ZJM-9 molecular sieve obtained in this example includes at least the following X-ray diffraction peaks:

[0057]

[0058] Among them, the incident ray of X-ray diffraction is Cu Kα1.

[0059] The water absorption capacity of the ZJM-9 molecular sieve product in this example was tested using a BELSORP-max II vapor adsorption instrument at 25°C. The water adsorption curve obtained is as follows: Figure 7 As shown in the figure, the upper curve is the water desorption curve, and the lower curve is the water adsorption curve.

[0060] Example 2

[0061] Place 5.07 g (concentration of 1.26 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 1.21 g of deionized water in a 25 ml beaker, add 0.93 g of boehmite (70 wt% Al2O3) and stir evenly, then add 1.03 g (concentration of 85 wt%) of phosphoric acid and stir for 2 hours to form a gel, add 0.08 g of solid silica gel, continue stirring for 2 hours, then pour into a hydrothermal reactor and crystallize at 200°C for 3 days.

[0062] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:0.7:0.2:1:40.

[0063] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0064] The sample was calcined at 400°C for 10 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.

[0065] 1g of calcined ZJM-8 molecular sieve was mixed with 20g of water and stirred at room temperature for 24 hours; after filtering and drying, it was calcined again at 100°C for 4 hours to obtain molecular sieve ZJM-9. Then it was ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-9, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0066] Example 3

[0067] 5.07 g (concentration of 1.26 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 0.57 g of deionized water were placed in a 25 ml beaker, 1.0 g of aluminum hydroxide was added and stirred evenly, and then 1.03 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; then the mixture was poured into a hydrothermal reactor and crystallized at 180°C for 7 days.

[0068] In the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: template: water is 1:1.3:1:40.

[0069] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0070] The sample was calcined at 800°C for 2 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.

[0071] 1g of calcined ZJM-8 molecular sieve was mixed with 20g of water and stirred at room temperature for 24 hours; after filtering and drying, it was calcined again at 800°C for 2 hours to obtain molecular sieve ZJM-9. Then it was ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-9, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0072] Example 4

[0073] 2.53 g (concentration of 1.26 mmol / g) of 1,4-hexaethylbutyl ammonium hydroxide aqueous solution and 2.36 g of deionized water were placed in a 25 ml beaker, 2.0 g of aluminum isopropoxide was added and stirred evenly, and then 1.92 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; 0.61 g (40 wt% SiO2) of silica sol was added and stirring was continued for 2 hours, and then poured into a hydrothermal reactor and crystallized at 200°C for 3 days.

[0074] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:1:0.5:1:40.

[0075] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0076] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.

[0077] 1g of calcined ZJM-8 molecular sieve was mixed with 20g of water and stirred at room temperature for 24 hours; after filtering and drying, it was calcined again at 550°C for 4 hours to obtain molecular sieve ZJM-9. Then it was ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-9, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0078] Example 5

[0079] 7.60 g (concentration of 0.89 mmol / g) of 1,4-hexaethylbutyl ammonium hydroxide aqueous solution was placed in a 25 ml beaker, 0.93 g of boehmite (70 wt% Al2O3) was added and stirred evenly, then 1.48 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; 0.12 g of fumed silica was added and stirring was continued for 2 hours, 0.68 g of water was dried off the gel under stirring, and finally poured into a hydrothermal reactor and crystallized at 200°C for 3 days.

[0080] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:1:0.3:1.5:20.

[0081] After the crystallization is completed, the hydrothermal reactor is cooled to room temperature, and the obtained molecular sieve is washed, filtered, and dried to obtain ZJM-8 molecular sieve. Then it is ground into powder for XRD analysis. The molecular sieve is a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern is similar to that of Example 1, and the diffraction peak data is similar to that of Example 1. The electron microscope photo shows that the molecular sieve is still in a hexagonal block.

[0082] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.

[0083] 1g of calcined ZJM-8 molecular sieve was mixed with 20g of water and stirred at room temperature for 24 hours; after filtering and drying, it was calcined again at 100°C for 10 hours to obtain molecular sieve ZJM-9. Then it was ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-9, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0084] Example 6

[0085] 7.60 g (concentration: 1.26 mmol / g) of 1,4-hexaethylbutylammonium hydroxide aqueous solution and 39.52 g of deionized water were placed in a 50 ml beaker, 0.65 g of Al2O3 was added and stirred evenly, and then 1.92 g (concentration: 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; then the mixture was poured into a hydrothermal reactor and crystallized at 250°C for 1 day.

[0086] In the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: template: water is 1:1:0.5:100.

[0087] After the crystallization, the hydrothermal reactor was cooled to room temperature, the obtained molecular sieve was washed, filtered, dried, and then ground into powder for XRD analysis. The molecular sieve was a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0088] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.

[0089] 1g of calcined ZJM-8 molecular sieve was mixed with 20g of water and stirred at room temperature for 24 hours; after filtering and drying, it was calcined again at 550°C for 4 hours to obtain molecular sieve ZJM-9. Then it was ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-9, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0090] Example 7

[0091] 7.60 g (concentration of 0.89 mmol / g) of 1,4-hexaethylbutyl ammonium hydroxide aqueous solution was placed in a 25 ml beaker, 0.93 g of boehmite (70 wt% Al2O3) was added and stirred evenly, then 1.48 g (concentration of 85 wt%) of phosphoric acid was added and stirred for 2 hours to form a gel; 0.80 g of tetraethyl silicate was added and stirring was continued for 2 hours, 0.68 g of water was dried off the gel under stirring, and finally poured into a hydrothermal reactor and crystallized at 200°C for 3 days.

[0092] Among the raw materials used in the above operation, the molar ratio of aluminum source calculated as Al2O3: phosphorus source calculated as P2O5: silicon source calculated as SiO2: template: water is 1:1:0.6:1.5:20.

[0093] After the crystallization is completed, the hydrothermal reactor is cooled to room temperature, and the obtained molecular sieve is washed, filtered, and dried to obtain ZJM-8 molecular sieve. Then it is ground into powder for XRD analysis. The molecular sieve is a new pure aluminum phosphate molecular sieve ZJM-8, and its XRD diffraction pattern is similar to that of Example 1, and the diffraction peak data is similar to that of Example 1. The electron microscope photo shows that the molecular sieve is still in a hexagonal block.

[0094] The sample was calcined at 550°C for 4 hours to obtain the calcined ZJM-8 molecular sieve. The molecular sieve structure remained unchanged, but the XRD diffraction peak position changed significantly, which was similar to the XRD diffraction pattern of the calcined ZJM-8 molecular sieve in Example 1, and the diffraction peak data was similar to that in Example 1. At the same time, the electron microscope photo showed that the morphology of the molecular sieve was still hexagonal block.

[0095] 1g of calcined ZJM-8 molecular sieve was mixed with 20g of water and stirred at room temperature for 24 hours; after filtering and drying, it was calcined again at 550°C for 4 hours to obtain molecular sieve ZJM-9. Then it was ground into powder for XRD analysis. The molecular sieve was aluminum phosphate molecular sieve ZJM-9, and its XRD diffraction pattern was similar to that of Example 1, and the diffraction peak data was similar to that of Example 1. The electron microscope photo showed that the molecular sieve was a hexagonal block.

[0096] Application examples in gas dehydration:

[0097] Take the ZJM-9 molecular sieve in Example 1 and use it in the following manner:

[0098] This experiment used a BSD-MAB multi-component adsorption breakthrough curve analyzer; 0.1 g of ZJM-9 molecular sieve was mixed with quartz wool and loaded into an 8 ml penetration column, purged with nitrogen at 200 °C for 2 hours, and then a mixed gas of water vapor and CH4 was introduced using nitrogen as the carrier gas, with a flow ratio of N2:CH4:H2O=185:3:12.

[0099] The outflow gas was analyzed by gas online mass spectrometry, and the H2O / CH4 competitive adsorption curve was as follows: Figure 8 In the figure, the upper part is the CH4 adsorption curve, and the lower part is the H2O adsorption curve. The separation factor of H2O to CH4 is 55.

[0100] It can be seen from the above results that the ZJM-9 molecular sieve in Example 1 can selectively remove water from methane gas.

[0101] Similar analysis results can be obtained by using the ZJM-9 molecular sieve in Example 2-7 in the same manner as above, so it can be confirmed that the phosphorus-aluminum-containing ZJM-9 molecular sieve prepared in the present invention plays a selective absorption role in gas dehydration.

[0102] Application examples in alcohol dehydration:

[0103] Take the ZJM-9 molecular sieve in Example 1 and use it in the following manner:

[0104] The experiments were conducted using a BSD-MAB multi-component adsorption breakthrough curve analyzer. 0.1 g of ZJM-9 molecular sieve was mixed with quartz wool and loaded into an 8 ml penetration column. The column was purged with nitrogen at 200 °C for 2 hours, and then a mixture of water vapor and CH3OH vapor was introduced using nitrogen as a carrier gas with a flow ratio of N2:CH3OH:H2O=185:3:12.

[0105] The outflow gas was analyzed by gas online mass spectrometry, and the H2O / CH3OH competitive adsorption curve was as follows: Fig. 9 In the figure, the upper part is the CH3OH adsorption curve, and the lower part is the H2O adsorption curve. The separation factor of H2O to CH3OH is 46.

[0106] It can be seen from the above results that the ZJM-9 molecular sieve in Example 1 can selectively remove water from methanol vapor.

[0107] Similar analysis results can be obtained by using the ZJM-9 molecular sieve in Example 2-7 in the same manner as above, so it can be confirmed that the phosphorus-aluminum-containing ZJM-9 molecular sieve prepared in the present invention plays a selective absorption role in alcohol dehydration.

[0108] Comparison with the adsorption capacity of calcined ZJM-8 molecular sieve:

[0109] The calcined ZJM-8 molecular sieve and the finally obtained ZJM-9 molecular sieve in Example 1 were used in the following manner:

[0110] 0.1 g of calcined ZJM-8 molecular sieve powder and ZJM-9 molecular sieve powder were taken respectively. After pretreatment at 300 °C for 10 hours, the N2 adsorption of the molecular sieves was measured at liquid nitrogen temperature. The adsorption curves are as follows: Fig.10 , 11 Analysis of the adsorption curve shows that the specific surface area of ​​ZJM-8 molecular sieve after calcination is 583m 2 / g, much larger than the specific surface area of ​​ZJM-9 molecular sieve 9m 2 / g.

[0111] 0.12 g of calcined ZJM-8 molecular sieve powder and ZJM-9 molecular sieve powder were taken and pretreated at 200 °C for 10 hours. The H2O vapor adsorption of the calcined ZJM-8 molecular sieve was measured at room temperature. The adsorption curves are as follows: Fig.12 , 13 Analysis of the adsorption curve shows that the water adsorption of the ZJM-8 molecular sieve after calcination is about 27wt.%, which is similar to the water adsorption of the ZJM-9 molecular sieve, which is about 25wt.%.

[0112] From the above results, it can be seen that ZJM-9 molecular sieve has a certain adsorption of H2O, which proves that the pores of ZJM-9 molecular sieve are open. At the same time, due to the specificity of the pores of ZJM-9 molecular sieve, compared with the calcined ZJM-8 molecular sieve, ZJM-9 molecular sieve can only adsorb water but not N2. Therefore, compared with the calcined ZJM-8 molecular sieve, ZJM-9 molecular sieve has a higher selectivity for water.

[0113] In the same manner as above, a comparative experiment on the adsorption capacity of the calcined ZJM-8 molecular sieve in Example 2-7 and the final ZJM-9 molecular sieve was carried out, and similar analysis results were obtained.

Claims

1. A method for preparing ZJM-9 molecular sieve containing phosphorus and aluminum components, characterized in that: The following steps are involved: (1) A template agent and water are prepared into a template agent solution, and an aluminum source, a phosphorus source and a silicon source are added in sequence under stirring, and the mixture is uniformly mixed to form a gel; wherein the molar ratio of the aluminum source calculated as Al2O3: the phosphorus source calculated as P2O5: the silicon source calculated as SiO2: the template agent: the water is 1: (0.7-1.3): (0-0.6): (0.5-1.5): (20-100); the template agent is 1,4-hexaethylbutyl diammonium hydroxide; (2) The gel is transferred to a hydrothermal reactor for hydrothermal crystallization reaction; the reaction temperature is 180-250 °C and the reaction time is 1-7 days; (3) filtering, washing and drying the product to obtain ZJM-8 molecular sieve; (4) calcining the ZJM-8 molecular sieve at a high temperature of 400 to 800° C. for 2 to 10 h to obtain a calcined ZJM-8 molecular sieve; (5) Mix the calcined ZJM-8 molecular sieve with water and stir evenly at room temperature; after filtering and drying the mixture, perform secondary calcination at 100-800°C for 2-10 h to obtain ZJM-9 molecular sieve, i.e., the phosphorus-aluminum-containing ZJM-9 molecular sieve product.

2. The method according to claim 1, characterized in that: The aluminum source is at least one of boehmite, aluminum hydroxide, aluminum oxide or aluminum isopropoxide.

3. The method according to claim 1, characterized in that The phosphorus source is phosphoric acid.

4. The method according to claim 1, characterized in that The silicon source is at least one of silica sol, fumed silica, solid silica gel or tetraethyl silicate.

5. Use of the ZJM-9 molecular sieve containing phosphorus and aluminum prepared by the method of claim 1 as an adsorbent.

Citation Information

Patent Citations

  • 1,4-hexaethyl butanediamine hydroxide, preparation method and application

    CN107235846A

  • Organic template agent, preparation method and application thereof, high-silicon KFI zeolite molecular sieve, and preparation method and application of high-silicon KFI zeolite molecular sieve

    CN114105166A

Cited By

  • Preparation method and application of ZJM-11 molecular sieve containing phosphorus and aluminum components

    CN122561972A